UPACARA ADAT YALAR ALIKARA PADA SUKU ALER DI KELURAHAN KOLANA UTARA KABUPATEN ALOR - Imanuel Besituba (Universitas 45 Surabaya, 2022)
This study aims to determine the mechanism of the Yalar Alikara Traditional Ceremony for the aler tribe in the North Kolana sub-district because the traditional ceremony is a tradition for every human being carried out by the aler tribe when applying for a bride to be a life partner and based on the beliefs of the aler tribe. It was explained that the tradition of the Yalar Alikara traditional ceremony for the Aler tribe in the North Kolana sub-district is a traditional ceremony that is visible and exists around human life which can always develop from time to time. Thus the traditional ceremony is a tradition carried out by humans around the aler tribe, both in the form of physical and non-physical. Both of which are very influential on the way humans carry out traditional ceremonies to build and maintain a household ark between the bride and groom properly.